Pemberdayaan Wirausaha Terdampak Covid-19 - Suriyadi, Suriyadi; Darmaji, Buyung (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
There are many ways that can be done in entrepreneurship, one of which is cultivating catfish livestock, so that it is successful both in preparing superior seeds and quality catfish seeds and harvesting, steps that can be taken include: 1) land for fish farming catfish. It can be divided into four parts, namely: type of land, far from settlements, accessible by vehicles, and according to the size of the land; 2) choosing a pool model, which can be divided into four parts, namely: earthen pool, cement pool, drum pool, and tarpaulin pool; 3) selection of catfish seeds, including: buying quality catfish seeds, cultivating catfish seeds, sorting process, transferring catfish fry, and catfish nursery; 4) the sowing of catfish seeds is divided into: pond water quality, time of sowing the seeds, and how to sow good catfish seeds; and 5) catfish rearing process as follows: pond water management, feeding, and sorting catfish. The marketing network for catfish livestock products that must be carried out includes: 1) utilizing social media as a means to promote good yields in the form of finished goods; 2) Cash On Delivery (COD) system or pay on the spot; 3) cooperate between traders or kiosks and provide a wholesale system; 4) cooperation system between sellers; 5) offering catfish to food stalls specifically for catfish; and 6) the group leader and members set up a food stall specifically for fresh catfish.